EFFECT OF FAVA BEAN EXTRACTS ON THE ERYTHROCYTE POTASSIUM TO HEMOGLOBIN RATION IN NORMAL SUBJECTS AND G6PD DEFICEICY PATIENTS - M. Rahmanian; M. Sadre; G. Donoso; H. Ghassemi; O. Mickelsen (Tehran University of Medical Sciences, 1979)
A procedure for the in vitro evaluation of the toxicity of fava beans has been applied to 17 varieties of the bean and one batch of beans purchased on the open market; the latter consisted of unknown varieties. The procedure involves the incubation of a saline extract of the beans with red cells from normal individuals and with red cells from G6PD deficient patients. 2. Normal red cells under those circumstances absorb potassium from the fava bean extract whereas the cells from G6PD deficient patients lose potassium. 3. This work suggest a relation between the toxicity of the fava beans and the lose of potassium by the red cells. On the basis of this assay, it appears that two of the 17 varieties may be non-toxic.